Compliance of plastic surgeons with advertising guidelines - Anthony Penna; Queenie Chan; Damian D Marucci (Australasian Journal of Plastic Surgery)
**Background**: Changes in the marketing of plastic surgery services in Australia has resulted in more plastic surgeons advertising on personal professional websites. The Australian Health Practitioner Regulation Agency (AHPRA) has produced guidelines for website advertising. This study evaluates the compliance of plastic surgeons with these advertising standards. **Method**: The professional websites for all members of the Australian Society of Plastic Surgeons (ASPS) were analysed. Websites were assessed in terms of their compliance with the AHPRA May 2014 ‘Guidelines for advertising regulated health services’. An assessment of each website was performed by two independent medical reviewers noting the use of deceptive advertising, gifts/discounts, comparison with other surgeons, website photos, inappropriate marketing phraseology to encourage surgery and the creation of unreasonable expectations. **Results**: All 309 ASPS members were included in the analysis. Seventy-five per cent of surgeons had a professional website. Over 80 per cent of ASPS members were fully compliant with the AHPRA advertising guidelines. Less than one percent of surgeons listed information considered to be misleading, deceptive, or creating unreasonable expectations. Gifts or discounts were offered by 5.8 per cent, 5.5 per cent used inappropriate marketing phraseology, 4.9 per cent made comparisons with other surgeons and 1.3 per cent had website photos that did not comply with recommended guidelines. Thirty-four per cent of surgeons were on Facebook, 20.4 per cent on Twitter and 19.4 per cent on Instagram. Of New South Wales surgeons, 13.8 per cent of had inappropriate website photos. Approximately 19 per cent of surgeons in Western Australia and South Australia used inappropriate marketing phraseology to encourage surgery. **Conclusion**: The majority of ASPS members are compliant with the national advertising guidelines. Regional non-compliance with specific areas was noted suggesting targeted education may be of benefit.